“Uma revolução democrática é sempre uma revolução inacabada” - or – “A democratic revolution must always remain unfinished” Commemorating the Portuguese 1974 revolution in newspaper opinion texts - Ribeiro, Filipa Perdigão (2012)
This article analyses the discursive construction of collective memories and the function of commemorative events for national identity. It focuses on how the 30th anniversary of the Portuguese 1974 revolution was portrayed in the government’s Programme of Action issued for the 2004 commemorations and in forty-three newspaper opinion articles also published in 2004. The 1974 revolution ended a 48-year right-wing dictatorship and has shaped subsequent historical events since the 1970s. When the Programme of Action changed the 1974 slogan ‘April is revolution’ into ‘April is evolution’, the written press responded by conducting a debate on this reframing. Using the Discourse-Historical Approach in CDA as the analytical framework, this paper highlights the discursive strategies on which the government’s manifesto was built and explores the opinion articles’ ongoing political and ideological tensions over the revolution, its commemorations, and how it paved the way into Europe, by describing the main macro-discursive strategies and raising issues regarding the (mis)representation of social actors and social action.